Interest in civil law - Pratasavitski, Sergey P. (Journal of the Belarusian State University. Law, 2020)
The concept of interest in civil law is explored in the paper, and, on that basis, proposals to improve the legislation are made. The interest is an independent type of receipt which is an additional monetary claim generated by monetary capital. The latter is understood as the main monetary claim arising from the provision of money with the obligation to return. It is proposed to introduce a general rule on the interest and place it outside of chapter 25 of the Civil Code of the Republic of Belarus. Simultaneously, the art. 366 of the Civil Code of the Republic of Belarus should be redrafted, providing for a statutory penalty for delayed performance of a monetary obligation. Indexation of any existing claim is not accepted. It should be replaced by the interest.